Student Perceptions Regarding E-Learning During the Covid-19 Pandemic on the Level of Technostress - Hania Pemilia; Yoni Hermawan; Bakti Widyaningrum (Jurnal Multidisiplin Madani, 2023)
The problem studied in this study was regarding the level of student technostress during the COVID-19 pandemic. This study aims to determine the effect of student perceptions of e-learning during the COVID-19 pandemic on students' technostress levels. This study uses quantitative research methods with explanatory survey research design. The population in this study were students of the economic education class 2019-2021. The sampling technique is simple random sampling, so a sample of 180 students is obtained as respondents in this study. Data collection was obtained by distributing questionnaires. The data analysis technique used is a simple linear regression test. The result of this study indicates that students' perceptions of e-learning and students' levels of technostress are in the high category. The study's result stated a significant effect of students' perceptions of e-learning on students' technostress levels with a sig value of 0.000 < 0,05. In other words, e-learning contributes to student's technostress by 20,7%